Knowledge on Covid-19 among undergraduate students in Universiti Putra Malaysia - Che Me, Nurul Samsiah; Abdul Rahman, Haliza; Abu Bakar, Azrin Shah (Human Resource Management Academic Research Society, 2022)
Since early June 2021, COVID-19 cases in Malaysia reported averagely above than 5000 positive cases a day. Regarding thefluctuate of positive cases, it is important to consider the knowledge on COVID-19 during the pandemic. Undergraduatesstudent population had selected to provide an image of their responses to pandemic. Objective: The aim of this study is to compare the score of the knowledge COVID-19 prevention among students in UPM. Methodology: A cross-sectional survey was conducted from 18 - 28 June 2021. Total of 310 respondents participated in this study, and classified by 3 groups which are health sciences, engineering and social science. Purposive sampling used where the participants have same interest of classified groups. Result and Discussion: A total of 95 (30.6%) respondents are male and 215 (69.4%) are female. The average knowledge score was 10.8 (SD = 1.5, range 0-13). There are significant different of knowledge score on COVID-19 between different group of students. Conclusion: The majority of undergraduate students were knowledgeable of the important facts in pandemic COVID-19.